Market and network corruption - Maria Kravtsova; Aleksey Oshchepkov (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2019)
Economists tend to reduce all corruption to impersonal market-like transactions, ignoring the role of social ties in shaping corruption. In this paper, we show that this simplification substantially limits the understanding of corruption. We distinguish between market corruption (impersonal bribery), and network (or parochial) corruption which is conditional on the social connections between bureaucrats and private agents. We argue, both theoretically and empirically, that these types of corruption have different qualities. Using data from the Life in Transition Survey (LiTS) which covers all post-socialist countries we show, first, that the correlation between market and network corruption is weak, which implies that ignoring network corruption leads not only to an underestimation of the overall scale of corruption but also biases national corruption rankings. Secondly, in line with theoretical expectations, we find that network corruption is more persistent over time, less related to contemporary national socio-economic and institutional characteristics and has stronger historical roots than market corruption. Yet, network corruption, unlike bribery, is not able to "grease the wheels" and is not associated with political instability. Lastly, we show that the decline in bribery which was observed in almost all post-socialist countries in the period from 2010 to 2016 was accompanied by rising network corruption in many of them, which has important policy implications.
urn:nbn:de:101:1-2019040812055258383446
Keywords: D73; Z13; L26; 330; market corruption; parochial corruption; network corruption; blat; bribery; postsocialist countries